Processos juntivos de causa em aquisição da escrita : uma abordagem de tradições discursivas - Silva, Patrícia Celene Senna da (2016)
In this work, which is inserted in the Grupo de Pesquisa Estudo sobre a Linguagem (GPEL/CNPq) and affiliated a bigger project called “Symptomatic Aspects of junction in the delimitation of Discursive Traditions”, we propose a particular approach to the conjunctive processes of cause, in context to the acquisition of Discursive Tradition (DTs) in written enunciation in order to describe and analyze the workings of these processes in formal and semantic-pragmatic fields. In this research, we based our choice of focusing in junction, generically, due to Kabatek hypothesis, which is confirmed in many of his studies (cf. KABATEK, 2000, 2005a, 2005b, 2005c, 2008) regarding the symptomatic aspects of conjunctive processes in DTs configuration, hence, in the hypothesis of correlation between junction and DTs. This choice is directed, specifically, by results of studies conducted in GPEL scope, for instance, Longhin (2011a, 2011b, 2014), Tuão-Brito (2014), Zago (2014), LopesDamasio (2011, 2013) which points cause relation as an wide universe for investigations in this matter. The analysis was composed by 100 sample texts produced by children in the old four first grades of Elementary School (ES1), thus, they experienced an institutionalized written language acquisition, focused on the general objective of gradually insert new writers in idiomatic rules (system and standard form) and in discursive rules (DTs). Therefore, the study reinforces Kabatek hypothesis (2005c) that the syntax can be glimpsed as an appropriate area for a coherent consideration of DTs, as well as an study that seeks to observe if regularities in linguistic evolution could be learned not only through the most typical paths of changing in time – phylogenesis – but also in acquisition paths – ontogenesis (KORTMANN, 1997). According to this hypothesis, we ask: “Do the mechanisms of causal junction, in texts from subjects in written acquisition reflect, anyhow, regularities observed in the development of junction in the history of language?”. In our analysis, we found great oscillation and not a linear sequencing along the four years, not only in the frequency of mechanisms but also in the semantic standards and in the pragmatic fields. This finding contributes for the written acquisition to not be treated as universal to all subjects and that this subject do not be idealized, because s/he is real and deals with language by his/her own way, through (his/her) consensual written image, by the influence of other and by written and oral practices which s/he is inserted and also by oral and written traditions that have/had contact.